One-year Survival Rate of Pancreatic Cancer and the Mortality Affecting Factors - Alexander Michael Joseph Saudale; Marcellus Simadibrata; Rino Alvani Gani; Cleopas Martin Rumende (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Pancreatic cancer is the fourth leading cause of death associated with malignancy in the United States, and is thought to be the second leading cause of death in 2030 in the United Kingdom. In Asia, pancreatic cancer is the most fatal cancer with the lowest survival of all malignancies, 25-30% survival five years after surgery. Indonesia has no data on the survival of pancreatic cancer and the factors that affect it. The aim of this study is knowing the 1-year survival of pancreatic cancer and its influencing factors in Cipto Mangunkusumo Hospital, Jakarta.Method: A retrospective cohort study was performed using data from the medical records of pancreatic cancer patients dr. Cipto Mangunkusumo Hospital between January 2012 - December 2016. Factors age, sex, metastasis, stage, comorbid and treatment were analyzed bivariate and multivariate using Cox Proportional Hazards Regression to obtain Hazard Ratio (HR) for each prognostic factor. The cumulative survival of 1 year after diagnosis is expressed by the Kaplan-Meier curve.Results: Of 83 subjects the proportion of males was 62.7%, age ≥ 50 years 68.7%, with age range 33-79 years, and 55 years on average. In bivariate analysis, there was a statistically significant relationship of survival with comorbid variables (HR = 2,116, 95% 953 1,335-3,513, p 0,002), metastasis (HR = 3,802, 95% CI: 1,995-7,249, p 0.001), palliative treatment (HR = 2,108 , 95% CI: 1,077-4,125, p = 0,029) and group without treatment (HR = 2,924, 95% CI: 1,496-5,716, p = 0,002). Multivariate analysis showed that metastasis provided the greatest risk of death with HR = 4.306 (95% CI: 2.125-8.724, p 0.001). Palliative group HR was 2.510 (95% CI: 1,245-5,061 p = 0.010) while the group without treatment gave HR 2,535 (95% CI: 1,277-5,032 p = 0,008). The 1-year survival rate is 14%, with a median survival of 6 months.Conclusion: The overall survival of one year of pancreatic cancer patients was 14%, with a median survival of 6 months. The presence of metastasis and not the curative therapy of Whipple surgery in patients with pancreatic cancer in dr. Cipto Mangunkusumo Hospital is the main factor that negatively affect the survival of 1 year